2023
DOI: 10.1038/s41598-023-31890-4
|View full text |Cite
|
Sign up to set email alerts
|

Abnormalities in intron retention characterize patients with systemic lupus erythematosus

Abstract: Regulation of intron retention (IR), a form of alternative splicing, is a newly recognized checkpoint in gene expression. Since there are numerous abnormalities in gene expression in the prototypic autoimmune disease systemic lupus erythematosus (SLE), we sought to determine whether IR was intact in patients with this disease. We, therefore, studied global gene expression and IR patterns of lymphocytes in SLE patients. We analyzed RNA-seq data from peripheral blood T cell samples from 14 patients suffering fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 51 publications
(82 reference statements)
2
3
0
Order By: Relevance
“…We observed a small-yet significant-inverse association between intron-retention-affected genes and their corresponding mRNA expression, specifically in SLE disease. Intron retention abnormalities have previously been described in active-SLE-patient-derived blood immune cells and is associated with the disrupted expression of the underlying genes [20,21]. This is also in line with the study of Ni et al [70], where most of the genes upregulated in CD4+ T-cells during activation had a reduction in intron retention due to enhanced mRNA stability [70].…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…We observed a small-yet significant-inverse association between intron-retention-affected genes and their corresponding mRNA expression, specifically in SLE disease. Intron retention abnormalities have previously been described in active-SLE-patient-derived blood immune cells and is associated with the disrupted expression of the underlying genes [20,21]. This is also in line with the study of Ni et al [70], where most of the genes upregulated in CD4+ T-cells during activation had a reduction in intron retention due to enhanced mRNA stability [70].…”
Section: Discussionsupporting
confidence: 82%
“…In agreement with the small number of shared genes, we found distinct molecular Intron retention represented the most prevalent class of AS among both SLE patients and healthy individuals (52.3% and 50.1% of sex-biased AS events, respectively) (Figure 1A,B). This predominance of intron retention events comes as a corroboration of recent data reported by us [21] and others [20] in the context of SLE. We observed a remarkable inverse relationship of intron retention events across the sex and disease state subgroups.…”
Section: Alternative Splicing Events Implicate Distinct Molecular Pat...supporting
confidence: 91%
See 1 more Smart Citation
“…The IR changes were further exemplified by the elevation of intronic expression in Pex12, Nkx3-2, Nkiras1, 1810026B05Rik, and the reduction of intronic expression in Tbx1 (Figure -1D-F). To analyze the intronic expression comprehensively at a gene-specific level, we employed IRI (intron reads index) analysis, which is an algorithm that quantifies the ratio of normalized read counts between intronic and exonic regions (Ni et al 2016;Sun et al 2023;Tian et al 2020). Subsequent analysis for retained introns demonstrated that Prmt1 deficiency-induced change in intron retention altered an array of biology pathways.…”
Section: Resultsmentioning
confidence: 99%
“…Recent evolution of the deep tech and artificial intelligence have enormously improved the outcome for the precise and accurate detection of intronic sequences among transcripts to assist in the diagnosis of intronic abnormalities and aberrant splicing events (Zheng et al, 2020). For instance, Sun et al (2023) employ the Intron Retention Index (IRI), an IRtools that provides IR analysis reads from RNA sequences collected from patients with systemic lupus erythematosus (SLE). The study reported dysregulation in IR as a hallmark of SLE disorder, which can be incorporate to enhance the accuracy of the IR detection.…”
Section: The Fate Of Intron Containing Transcriptsmentioning
confidence: 99%